Income distribution determinants and public spending efficiency - António Afonso; Ludger Schuknecht; Vito Tanzi (European Central Bank (ECB), 2008)
In this paper we examine the impact of public spending, education, and institutions on income distribution in advanced economies. We also assess the efficiency of public spending in redistributing income by using a DEA (Data Envelopment Analysis) nonparametric approach. We find that public policies significantly affect income distribution, notably via social spending, and indirectly via high quality education/human capital and via sound economic institutions. Moreover, for our set of OECD countries, and within a two-step approach, several so-called non-discretionary factors help explaining public social spending inefficiencies.
Keywords: C14; H40; H50; 330; DEA; Efficiency; income redistribution; public spending; Einkommensverteilung; Umverteilung; Öffentliche Ausgaben; Bildungsinvestition; Institutionelle Infrastruktur; Data-Envelopment-Analyse; OECD-Staaten